Neumotórax asociado a neumonía por SARS-CoV-2 - Maria Inês Luz; Luís Carreto (Sociedade Galega de Medicina Interna, 2021)
The coronavirus disease 2019 (COVID-19) is a recent outbreak in mainland China and has rapidly spread to multiple countries worldwide. COVID-19 infection causes a severe lower respiratory tract infection with bilateral, basal and peripheral predominant ground-glass opacity, consolidation or both as the most common reported chest CT findings. Pleural effusion and pneumothorax are uncommon but may be seen with disease progression. We present a case of a 70-year-old male who presented with spontaneous pneumothorax and SARS-CoV-2 pneumonia.